STRATEGI OPTIMALISASI IVA TEST MELALUI PEMBERDAYAAN KADER DENGAN PENERAPAN MODUL PROMOSI KESEHATAN TENTANG DETEKSI DINI KANKER SERVIKS DI KELURAHAN BARATAN KEC. PATRANG KAB. JEMBER - AINUL HIDAYATI (LPPM Universitas dr. Soebandi, 2025)
Cervical cancer is the second most common cancer in women worldwide and the seventh most common cause of cancer death in women. Breast cancer and cervikal cancer are one of the most common cancer in inonesia. Through health promotion in the form of providing health education and implementing modules on early detection of cervical cancer, it is hoped that knowledge and skills will be increased in carrying out early detection of cervical cancer through the IVA Test. The aim of community service is to optimize the abilities and skills of posyandu cadres in implementing the early detection module for cervical cancer and the IVA Test. The implementation of this health education activity begins at the cadre stage, their knowledge will first be measured through a pre-test. Health education activities were carried out by giving lectures and discussions as well as distributing modules about cervical cancer and IVA Test examinations. After the health education activities, cadres will again have their knowledge measured with a post test. It is hoped that this activity can be a starting point for the community to increase the optimization of the IVA Test independently by coordinating with other surrounding agencies and resources. Based on this research, it was found that mothers' knowledge increased after being given education. So it is important to improve knowledge and skills related to early detection of cervical cancer.